Pengaruh Tarif Pajak, Modernisasi Administrasi Perpajakan Dan Keadilan Pajak Terhadap Kecenderungan Tax Evasion - Luh Ika Apriyani; Ni Ketut Muliati; I Wayan Budi Satriya (UNHI Press, 2023)
Measures or efforts are needed to improve taxpayer tax payment so that tax evasion does not occur. Tax evasion trends can be caused by several factors, including:B. Tax Rates, Modernization of Tax Administration, and Tax Equity. The purpose of this study was to determine the impact of tax rates, modernization of tax administration, and tax law on tax evasion trends (case study at KPP Pratama East Denpasar). The population for this study is his KPP Pratama East Denpasar individual taxpayers in 2022, totaling 137,453. In this study, the sample size was 100 subjects determined by random sampling technique and tested by multiple regression analysis technique. The results of this study show that tax rates have a positive and significant effect on the propensity to evade tax. Tax administration reform and tax justice have a significant negative impact on tax evasion trends.